Modelo de desenvolvimento de soluções conceituais de forno de carbonização - Rodrigues, Thaisa (2019)
Most of the world's charcoal production comes from low-tech kilns, resulting in high variability in charcoal yield and quality. Given that charcoal plays an important role as a bioreductor in Brazilian steel production, it is necessary to invest in the development and improvement of traditional charcoal production technologies. The kiln development process usually has an experimental character and is not usually structured and formalized. To aid the innovation process in the design of carbonization kilns, this work aimed to build a model for developing conceptual carbonization kiln solutions. To this end, a technological prospecting of charcoal production was carried out from patent studies and scientific work on carbonization kilns. The informational design and the main stages of the carbonization kiln conceptual design were also elaborated, as well as the definition of the general kiln evaluation criteria and conceptual solution prioritization criteria, as well as the relationship between these criteria and the main characteristics of the kilns. Subsequently, the development model of conceptual kiln solutions was elaborated, which has a multicriteria analysis method for its prioritization. With the application of the model it was possible to prioritize the most suitable oven concept in comparison to the others, helping the designer to better explore the possibilities (conceptual oven solutions) and to think more creatively, freely and not necessarily tied to conventional ideas. Moreover, with the model it is possible to make more consistent choices, prioritizing the most promising conceptual designs. Thus, the model was validated and thus demonstrated its viability.